Dissociative disorders and other psychopathological groups: exploring the differences through the Somatoform Dissociation Questionnaire (SDQ-20) - Espirito-Santo, Helena (2006)
The Somatoform Dissociation Questionnaire is a self-report questionnaire that has proven to be a reliable and valid instrument. The objectives of this study were to validate the Portuguese version and to determine its capability to distinguish patients with dissociative disorders from others with psychopathological disorders. Method: 234 patients answered the translated version of Somatoform Dissociation Questionnaire. The Portuguese Dissociative Disorders Interview Schedule was used to validate clinical diagnosis. Patients with dissociative disorder (n = 113) were compared to a control group of 121 patients with various anxiety and depression disorders. Results: Reliability measured by Cronbach’s α was 0.88. The best performance of the Portuguese form was at a cut-off point of 35, which distinguishes between dissociative disorder and neurotic disorders with a good diagnostic efficacy (sensitivity = 0.73). The somatoform dissociation was significantly more frequent in dissociative disorder patients, conversion disorder patients and post-traumatic stress disorder patients. Conclusions: These findings suggest that dissociative disorders can be differentiated from other psychiatric disorders through somatoform dissociation. The Portuguese version of the Somatoform Dissociation Questionnaire has fine psychometric features that sustain its cross-cultural validity.